Azole susceptibility patterns and genetic relationship among oral Candida strains isolated in the era of highly active antiretroviral therapy - Tacconelli, Evelina; Bertagnolio, Silvia; Posteraro, Brunella; Tumbarello, Mario; Boccia, Stefania; Fadda, Giovanni; Cauda, Roberto (Journal of acquired immune deficiency syndromes (1999), 2002)
We performed a cross-sectional study to analyze patterns of azole susceptibility of oral isolates in the highly active antiretroviral therapy (HAART) era and compared current data with those obtained for isolates from 1994. We further identified patients with relapsing oral pharyngeal candidiasis (OPC) who had been included in a similar study in 1994. For these subjects, we compared the susceptibility pattern for the OPC isolates, and if a modification of azole resistance was observed, we analyzed the genotypic pattern for the 1994 and 2000 isolates to determine whether the dominant strain was closely related. We included 69 consecutive HIV-infected subjects with 137 episodes of OPC who were admitted to our ward from January to June 2000. Ninety-two strains (67%) and 21 non- strains (15%) were isolated. We identified 24 episodes of OPC caused by two different species. Compared with the pre-HAART era, the fluconazole resistance of isolates significantly decreased from 45% to 10% (p <.001). Itraconazole resistance decreased from 37% to 7% (p <.001). Ketoconazole resistance (3% in 1994) was not detected more. Nine patients whose isolate was susceptible to all azole drugs had a previous isolate resistant to all azole drugs. We observed that these isolates exhibited different fingerprint profiles. Our findings demonstrate that most cases of HIV-associated OPC observed in the HAART era are caused by azole-susceptible strains. The reversion of an isolate from azole resistant to azole susceptible is related to strain replacement.